Effect of hierarchical Fartelk training on speed tolerance and Oxygen intolerance of aggressors (2000 m) Contraindications - Ali Hussein Ali Al-Bahadly; Karim Naima Rhan AL-Kaabi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The aim of the research was to prepare training units in the pyramidal method to develop the ability to withstand the speed and the ability of the muscular oxygen endurance of the hostile (2000) contraindications. The researchers used the tools, tools and tests to complete the research procedures, and the researchers used the experimental approach, one-group design to suit the nature of the research, and the researchers conducted their main experiment for a period of (13 weeks) starting Monday On 3/12/2018 until 4/3/2019 corresponding to Monday (92 days), and two training units per week, the total total units (26 training modules), and the researchers used the statistical bag (spss), and the researchers reached the most important conclusions that The pyramidal training showed an improvement in the speed of endurance and muscular endurance. The researchers also recommended the use of pyramidal training within the vocabulary of the training program (2000 m).